Sejam $f ,g : \mathbb{R}\to \mathbb{R}$ funções tais que: $g(x) = 1- x$ e $f (x) + 2f (2 - x ) = ( x - 1)^3$ para todo $x \in \mathbb{R}$. Então $f [g(x)]$ é igual a:


img
ITA IIIT 28/10/2021 15:50
Fazendo $f \circ g$: \begin{matrix} f[g(x)] + 2\cdot f[2 - g(x)] = (g(x)-1)^3 \\ \\ g(x) = 1-x \\ \\ f[g(x)] + 2\cdot f(1+x) = (-x)^3 \ \ \color{#3368b8}{(1)} \end{matrix} $\color{orangered}{Obs:}$ $f[g(x)] = f(1-x)$ Seja $h(x) = 1+x$, façamos $f \circ h$: \begin{matrix} f[h(x)] + 2\cdot f[2 - h(x)] = (h(x)-1)^3 \\ \\ f(1+x) + 2\cdot f(1-x) = (x)^3 \\ \\ f(1+x) + 2\cdot f[g(x)] = (x)^3 \ \ \color{#3368b8}{(2)} \end{matrix}Resolvendo o sistema composto por $(1)$ e $(2)$: \begin{matrix} f[g(x)] = x^3 \\ \\ Letra \ (C) \end{matrix}
Modo de Edição
0 / 5000
ManualLaTeX